Low-Dose Dose–Response for In Vitro Nrf2-ARE Activation in Human HepG2 Cells. Issue 2 (18th April 2017) - Bogen, Kenneth T.
Kelch-like ECH-associated protein 1 (Keap1), nuclear factor erythroid 2-like factor 2-related factor 2 (Nrf2), and the antioxidant response element (ARE) are interacting components of a master regulatory signaling pathway that coordinates redox homeostasis, cytoprotective responses, and shifts in stem cell state. This study reexamined detailed dose–response (DR) data reported for in vitro Nrf2-ARE activation in human hepatoblastoma HepG2 cell lines containing either a ARE- bla or ARE- luc reporter at 12 different concentrations of each of 15 chemicals. The normalized study data were combined among chemicals exhibiting a positive response, yielding n = 531 (179) DR data for 9 (7) chemicals using the ARE- bla (ARE- luc ) assay. Three-parameter linear/ k th-power regression fits obtained to each combined set of ARE- bla - or ARE- luc -assay response data provided good fits ( R 2 = .99 or .91, respectively, P fit > .99) that each incorporate a highly significant negative initial linear slope ( P = 4 × 10 −5 or .00025) and an overall J-shaped DR pattern. Results from this reanalysis of high-resolution ARE response data support the hypothesis that nonlinear ARE-mediated adaptive cellular responses to oxidative stress are governed by an ultrasensitive molecular switch.